Effects of spatial aggregation of nests on population recruitment: the case of a small population of Atlantic salmon. Issue 4 (12th April 2018) - Bouchard, Colin; Bardonnet, Agnès; Buoro, Mathieu; Tentelier, Cédric
Abstract: Spatial aggregation within a population is a widespread phenomenon which may both exacerbate local competition and the stochastic effect of local environmental perturbations. In particular, the spatial aggregation of nests may strongly affect recruitment and hence population dynamics. Although the negative effect of local density on local recruitment has often been theoretically extended to population dynamics, very few studies have demonstrated the effect of local aggregation on the whole population recruitment. Using a long‐term survey of a small Atlantic salmon population, we tested the effect of spatial aggregation on the whole population recruitment and whether accounting for population stock is important or not when explaining the population recruitment. We found that accounting for population stock is necessary and that spatial aggregation of nests improved estimates of population recruitment. The spatial aggregation of nests did not impact the average population recruitment; however, a stronger aggregation diminished the variability of population recruitment. Our findings suggest that the aggregation of nests among some breeding areas does not necessarily impair the whole population recruitment and significantly reduces the stochasticity of the recruitment. In addition, the aggregation of nests seems to be the result of an ideal distribution of females, selecting the best‐breeding sites. Our results also indicate that females select breeding sites on environmental risk to spawn within the safest sites. This study warns against the extrapolation of local density dependence observations to the population level, and advocates for investigating the effect of aggregation on the demographic and evolutionary population dynamics, a clear contribution of aggregation on population dynamic processes being found in the Nivelle population.